Geo-Social Media and Socio-Territorial Distribution: A Study on the Italian Case - De Falco, Antonio; De Falco, Ciro Clemente; Ferracci, Marco (Italian Sociological Review, 2022)
In the data revolution era, new data and new sources allow researchers to find new ways to study society and its dynamics. Among these types of data, geo-located data enable better ways of producing social knowledge. The availability of data with geographic information put the spatial dimension – initially ignored in social media analysis – at the centre of the interest in digital and web studies. In addition, this data also makes it possible to address the representativeness of big data innovatively. For this reason, we explore the territorial distribution of geo-located tweets regarding some significant territorial socio-economic dimensions in Italy. Our main results show a concentration of users in specific macroareas, a direct proportionality between the size of the city and tweets number, and more users in the urban centre than in metropolitan suburbs. In conclusion, we try to identify the factors underlying these differences and their implications in terms of data analysis and representativeness of the results.